2011
DOI: 10.1038/nchembio.598
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule displacement of a cryptic degron causes conditional protein degradation

Abstract: The ability to rapidly regulate the functions of specific proteins in living cells is a valuable tool for biological research. Here we describe a novel technique by which the degradation of a specific protein is induced by a small molecule. A protein of interest is fused to a Ligand-Induced Degradation (LID) domain resulting in the expression of a stable and functional fusion protein. The LID domain is comprised of the FK506- and rapamycin-binding protein (FKBP) and a 19-amino acid degron fused to the C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 29 publications
2
161
0
2
Order By: Relevance
“…A potential limitation of the Degron-KI approach is that it only works efficiently when applied as an N-terminal fusion (10, and data not shown) and thus requires that proteins can tolerate N-terminal tagging. While Cterminal degron fusion systems have been described (36,37), we found that protein depletion was much less effective compared with the DD-Shld system (data not shown). In addition, for some genes the expression level of DD-tagged protein was reduced compared with the untagged protein, possibly due to slight alteration in protein stability (incomplete stabilization through Shld) or translation efficiency (due to the P2A ribosome skipping site).…”
Section: Discussionmentioning
confidence: 60%
“…A potential limitation of the Degron-KI approach is that it only works efficiently when applied as an N-terminal fusion (10, and data not shown) and thus requires that proteins can tolerate N-terminal tagging. While Cterminal degron fusion systems have been described (36,37), we found that protein depletion was much less effective compared with the DD-Shld system (data not shown). In addition, for some genes the expression level of DD-tagged protein was reduced compared with the untagged protein, possibly due to slight alteration in protein stability (incomplete stabilization through Shld) or translation efficiency (due to the P2A ribosome skipping site).…”
Section: Discussionmentioning
confidence: 60%
“…FK506 induced ID1 at low doses, and a high plateau of activation was rapidly achieved. We then compared the effect of FK506 and rapamycin to another calcineurin inhibitor, cyclosporine, that does not interact with FKBP12 but binds the immunophilin, cyclophilin A, as well as shield-1 (27). Shield-1 binds FKBP12 but does not have any immunosuppressive properties ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…For example, using a procedure named deGradFP, proteins fused to green fluorescent protein (GFP) can be depleted by expressing a fusion protein consisting of an anti-GFP antibody coupled to an F-box domain; the fusion protein recruits GFP-tagged protein to SKP1-CUL1-F-box (SCF) E3 ubiquitin ligase complexes, marking it for ubiquitylation and proteasome-mediated degradation (Caussinus et al, 2012). deGradFP has been shown to degrade target proteins over a period of 2-3 hours (Caussinus et al, 2012), comparable with the kinetics of most other protein degradation strategies (Bonger et al, 2011;Taxis et al, 2009;Zhou et al, 2000). However, many developmental events occur on a much faster timescale.…”
Section: Introductionmentioning
confidence: 98%
“…Strategies include introducing temperature-sensitive protease cleavage sites, or using heterologous adaptor proteins, drugs or light to induce the ubiquitin-mediated degradation of a tagged target protein (Banaszynski et al, 2006;Bonger et al, 2011;Nishimura et al, 2009;Raina and Crews, 2010;Renicke et al, 2013). For example, using a procedure named deGradFP, proteins fused to green fluorescent protein (GFP) can be depleted by expressing a fusion protein consisting of an anti-GFP antibody coupled to an F-box domain; the fusion protein recruits GFP-tagged protein to SKP1-CUL1-F-box (SCF) E3 ubiquitin ligase complexes, marking it for ubiquitylation and proteasome-mediated degradation (Caussinus et al, 2012).…”
Section: Introductionmentioning
confidence: 99%